2023
DOI: 10.1111/bcpt.13848
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate alleviates intracerebral haemorrhage secondary injury by inducing ferroptosis in M1‐polarized microglia and suppressing inflammation through AMPK/mTORC1/GPX4 pathway

Abstract: Intracerebral haemorrhage (ICH) is a catastrophic subtype of stroke with severe morbidity and mortality. However, little progress has been made in the subsequent secondary injury. Artesunate, a water-soluble semi-synthetic derivative of artemisinin, exhibits remarkable pharmacological effects on anti-neuroinflammation. However, the effects of artesunate on ICH remain unknown.In the present study, haemoglobin (Hb) treatment in BV2 cell and collagenase type IV intracerebroventricular injection in Sprague-Dawley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Advancements in ferroptosis research have led to the discovery of a series of approved drugs (e.g. sulfasalazine [ 69 ], artesunate [ 70 ], sorafenib [ 71 ], acetaminophen [ 72 ]) that could induce ferroptosis. Moreover, there is an increasing emphasis on utilizing ferroptosis targets and regulators as the basis for large-scale screening of small-molecule drugs or developing larger-molecule drugs, such as specific antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Advancements in ferroptosis research have led to the discovery of a series of approved drugs (e.g. sulfasalazine [ 69 ], artesunate [ 70 ], sorafenib [ 71 ], acetaminophen [ 72 ]) that could induce ferroptosis. Moreover, there is an increasing emphasis on utilizing ferroptosis targets and regulators as the basis for large-scale screening of small-molecule drugs or developing larger-molecule drugs, such as specific antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to artemisinin, artesunate (a culture containing 0–60 μM artesunate for 24 h) inhibited the expression of TLR4 and MyD88, and the activation of NF-κB via blocking the degradation of IκB, suggested that artesunate might inhibit the production of pro-inflammatory mediators by suppressing TLR4/MyD88/NF-κB signaling pathway [ 84 ]. What's more, artesunate ameliorated intracerebral haemorrhage (ICH) secondary injury in vitro (at 2, 5, 10, and 15 μM was added 24 h after Hb treatment) and in vivo (rats received artesunate at 20, 50 or 70 mg/kg/day via i. p. injection for 3 consecutive days before ICH induction) by inducing microglial cell iron death and further inhibiting inflammation mainly through the AMPK/mTORC1/GPX4 pathway [ 85 ]. This finding may provide a new target for the treatment of ICH.…”
Section: The Role Of Arts In the Treatment Of Autoimmune And Inflamma...mentioning
confidence: 99%
“…AMPK is an energy sensor widely present in various tissues and cells. For instance, when it is present in brain tissue and microglial cells, it can alleviate secondary damage from cerebral haemorrhage ( 92 ). It regulates cellular energy metabolism balance ( 93 ), and participates in the regulation of multiple biological processes, including glycogen synthesis ( 94 ), fatty acid synthesis ( 95 ) and mitochondrial biogenesis ( 96 ).…”
Section: Ferroptosis-associated Pathways In Strokementioning
confidence: 99%
“…In vitro experiments showed a phosphorylation reaction of AMPK after initial intervention with AMPK inhibitors in BV2 cells. Subsequently, pharmacological intervention led to upregulation of ROS and lipid peroxidation levels (positive regulators of ferroptosis) in BV2 cells, and silenced GPX4 (a key negative regulator of ferroptosis) levels through the AMPK signaling pathway ( 92 ). In in vivo experiments, iron deposition at the site of brain injury was observed through Perl's staining ( 92 ).…”
Section: Ferroptosis-associated Pathways In Strokementioning
confidence: 99%
See 1 more Smart Citation